Laboratory Examination of Syphilis - M. Izazi Hari Purwoko; Mutia Devi; Suroso Adi Nugroho; Fitriani Fitriani; Raden Pamudji; Nofilia Citra Candra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Syphilis, is sexually transmitted disease caused by spirochete Treponema pallidum subsp.pallidum. It have many diverse clinical manifestations that occur in distinct stages. Early diagnosis and management are the main things to prevent transmission and complication. Direct test or morphological observation is the definitive diagnosis of syphilis. This can be done through animal inoculation test, dark field microscopy, direct fluorescence antibody (DFA), and nucleid acid amplification test (NAAT). While the indirect test is a nontreponemal serologic test consist of Wasserman test, venereal disease research laboratory (VDRL), toluidine red unheated serum test (TRUST), unheated serum reagin (USR), rapid plasma reagin (RPR) and treponemal serologic test, such as T. pallidum passive particle agglutination (TPPA), T. pallidum haemagglutination assay (TPHA), fluorescent treponemal antibody absorption (FTA-Abs), enzyme immunoassay (EIA) and rapid test. The algorithm of serologic test can be divided into traditional or reverse.